Misogyny incubators: how gaming helps channel everyday sexism into violent extremism - Miller-Idriss, Cynthia (Frontiers in Psychology, 2025)
We face a pervasive and proliferating climate of online misogyny, along with an ever-expanding digital ecosystem that makes it faster and easier to express and share hateful content and harass individuals. In this review article, I explore one explanation for how online misogyny has become so ubiquitous and mainstream, looking at how online and digital gaming communities incubate, channel, and champion hostile sexist and misogynist attitudes, dehumanizing slurs, and other hateful content directed toward women and gender non-conforming people. I situate this mainstreaming of online misogyny within a broader rise of male supremacist violence, including threats, plots, and attacks from misogynist incels, noting that gender-based violence is a demonstrated precursor to and occasional mobilizer of mass violence. Case examples draw heavily on the U.S. and on English-language slurs and epithets to ultimately argue that while some online misogyny and harassment is deliberate and organized through targeted troll storms or violent plots and attacks, other aspects of the new misogyny are decidedly mainstream and ubiquitous in spaces and places frequented by boys and men, such as in-game chats in digital gaming, in ways that potentially foment, normalize, and mobilize significant violence.